Zigzag nanoribbons of two-dimensional silicene-like crystals: magnetic, topological and thermoelectric properties. (13th November 2015) - Wierzbicki, Michał; Barnaś, Józef; Swirkowicz, Renata
Abstract: The effects of electron–electron and spin–orbit interactions on the ground-state magnetic configuration and on the corresponding thermoelectric and spin thermoelectric properties in zigzag nanoribbons of two-dimensional hexagonal crystals are analysed theoretically. The thermoelectric properties of quasi-stable magnetic states are also considered. Of particular interest is the influence of Coulomb and spin–orbit interactions on the topological edge states and on the transition between the topological insulator and conventional gap insulator states. It is shown that the interplay of both interactions also has a significant impact on the transport and thermoelectric characteristics of the nanoribbons. The spin–orbit interaction also determines the in-plane magnetic easy axis. The thermoelectric properties of nanoribbons with in-plane magnetic moments are compared to those of nanoribbons with edge magnetic moments oriented perpendicularly to their plane. Nanoribbons with ferromagnetic alignment of the edge moments are shown to reveal spin thermoelectricity in addition to the conventional one.